Structural Diversity in Galactans From Red Seaweeds and Its Influence on Rheological Properties - Ciancia, Marina; Matulewicz, María Cristina; Tuvikene, Rando (Frontiers in Plant Science, 2020)
Galactans are important components of many plant cell walls. Besides, they are the major polysaccharides in extracellular matrixes from different seaweeds, and other marine organisms, which have an acidic character due to the presence of sulfate groups in their structures. In particular, most of the red seaweeds biosynthesize sulfated galactans with very special linear backbones, constituted by alternating (13)--D-galactopyranose units (A-unit) and (14)--galactopyranose residues (B-unit). In the industrially significant seaweeds as source of hydrocolloids, B-units belong either to the D-series and they produce carrageenans (as in the order Gigartinales), or to the L-series, and they are sources of agarose and/or structurally related polymers (i.e., Gelidiales, Gracilariales). In both cases, the latter units appear as cyclized 3,6-anhydro--galactose in certain amounts, which can be increased by alkaline cyclization of -galactose 6-sulfate units. Besides, it has been clearly shown that some red algae produce different amounts of both galactan structures, known as D/L-hybrids. It is not yet clear if they comprise both diasteromeric types of units in the same molecule, or if they are mixtures of carrageenans and agarans that are very difficult to separate. It has been reported that the biosynthesis of these galactans, showing that the nucleotide transport for D-galactopyranose units is UDP-D-Gal, while for L-galactose, it is GDP-L-Gal, so, there is a different pathway in the biosynthesis of agarans. However, at least in those seaweeds that produce carrageenans as major galactans, but also agarans, both synthetic pathways should coexist. Another interesting characteristic of these galactans is the important variation in the sulfation patterns, which modulate their physical behavior in aqueous solutions. Although the most common carrageenans are of the κ/- and λ-types (with A-units sulfated at the 4- and 2-positions, respectively) and usually in agarans, when sulfated, is at the 6-position, many other sulfate arrangements have been reported, greatly influencing the functional properties of the corresponding galactans. Other substituents can modify their structures, as methyl ethers, pyruvic acid ketals, acetates, and single stubs of xylose or other monosaccharides. It has been shown that structural heterogeneity at some extent is essential for the proper functional performance of red algal galactans.